Parent’s acceptance on wearable technology for children’s safety - Zadilhayat Mohammed; Fauziah Redzuan (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper presents a study on parent’s acceptance on wearable technology for children’s safety. Recently, there are many applications of wearable technology used in ensuring children’s safety, such as GPS tracking devices that are seen to be related to the safety of the children. However, the Malaysian parents have not been using these technologies to protect their children due to lack of knowledge on the wearable technology, non-familiarity with the devices, privacy and also security concern of data in wearable technology. Thus, the objective of the present research is to identify the significant factors that influence parents’ acceptance on wearable technology for their children’s safety and to identify the greatest influence factors for the acceptance of these wearable technologies for children’s safety. These factors are expected to bring about usefulness, ease of use, trust, privacy risk, financial risk and intention to use these technologies. As such, quantitative survey method was employed in the present study to obtain the result for the factors acceptance. The analysis and findings were done using IBM SPSS Version 25 tools via Pearson Correlation Analysis and Multiple Linear Regressions to get the result for the acceptance and to achieve the research objectives. Based on the result, it is discovered that the factors significant to intention to use of the wearable technology are perceived usefulness, perceived ease of use and trust while privacy and financial risk are factors seen to be non-significant to intention to use the wearable technology. Lastly, trust is discovered to be the greatest factor influencing parents to accept wearable technology and intention to use the technology. However, it is recommended for further study to employ experimental method in carrying out the research in order to get the real trust feeling of intention to use the wearable technology.